Pengaruh PGPR dan Pupuk Kandang terhadap Pertumbuhan dan Hasil Tanaman Paprika (Capscium annuum, L.) di Dataran Rendah - Bagus Agil Anshori; Mohamad Ihsan; Libria Widiastuti (​Institute for Researches and Community Services Universitas Muhammadiyah Palangkaraya, 2022)
This study was done on December, 2020 until April, 2021, at an altitude ofp+125 meters above sea level in Palur Village, Mojolaban District, Sukoharjo Regency, Central of Java. The purpose ofithis study is to know how PGPR and various types ofpmanure affect on growth and yield ofppaprika (Capsicum annuum L.) in the lowlands. This study used an environment with a Completely Randomized Design (CRD) basic pattern, followed by a 5% DMRT test with considerably different outcomes. Two factors and four replicates made up the treatment factor. The first element was the availability of PGPR, which was divided into two tiers (P0: without the use of PGPR, P1: the use of PGPR). The second factor was the provision of various forms of manure, which was divided into three kinds (M1: chicken manure, M2: goat manure, and M3: cow manure). Plant height, fruit weight, number of fruits, fruit diameter, fresh weight of stover, and driedweight of stover were all observed metrics. The results showed that the PGPR treatment had a substantial effect on the parameters ofpfruit weight and fresh weight of stover, as well as on the parameters of fruit diameter and dry weight of stover, but not significantly different on the parameters ofpplant height andpnumber ofpfruit, while the effect ofpthe use of various types of manure showed a very significant effect on all parameters. The treatment with cow manure had the best effect on paprika growth and yield. The combination between PGPR treatment and various types of manure had a substantial impact on fresh stover characteristics as well as fruit weight, However, plant height, quantity of fruits, diameter, and dry stover were not significantly different. The application of PGPR and cow manure was the best treatment combination for paprika growth and yield.